2018
DOI: 10.1021/acs.jafc.7b05131
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Reveal Optimal Grain Preprocessing (Milling) toward Rice Koji Fermentation

Abstract: A time-correlated mass spectrometry (MS)-based metabolic profiling was performed for rice koji made using the substrates with varying degrees of milling (DOM). Overall, 67 primary and secondary metabolites were observed as significantly discriminant among different samples. Notably, a higher abundance of carbohydrate (sugars, sugar alcohols, organic acids, and phenolic acids) and lipid (fatty acids and lysophospholipids) derived metabolites with enhanced hydrolytic enzyme activities were observed for koji made… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…All BR samples at five levels of DOMs (i.e., 5, 7, 9, 11, and 13 DOM) were polished using a rice polishing machine (NRH-500, Narok Co., Ltd., Hwaseong-si, Korea). Each DOM is defined in terms of the proportion of embryo and bran layer remaining in the whole rice grain [ 6 ]. Therefore, BR, 5, 7, 9, 11, and 13 DOM indicate that 100%, 50%, 30%, 15%, 5%, and 0% of the embryo and bran layer in the rice grain are retained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All BR samples at five levels of DOMs (i.e., 5, 7, 9, 11, and 13 DOM) were polished using a rice polishing machine (NRH-500, Narok Co., Ltd., Hwaseong-si, Korea). Each DOM is defined in terms of the proportion of embryo and bran layer remaining in the whole rice grain [ 6 ]. Therefore, BR, 5, 7, 9, 11, and 13 DOM indicate that 100%, 50%, 30%, 15%, 5%, and 0% of the embryo and bran layer in the rice grain are retained.…”
Section: Methodsmentioning
confidence: 99%
“…A DOM of rice between 5 and 11 indicates the retention of 50% and 5% of the embryo and bran layer, respectively, for BR. Additionally, rice with a DOM of 13 typically does not contain an embryo or an aleurone layer [ 6 ]. Rice with a DOM >10 is generally referred to as white (polished) rice.…”
Section: Introductionmentioning
confidence: 99%
“…Physicochemical characteristics were evaluated as described by Lee et al with some modifications [60]. An FSP sample (3 g) was mixed with 30 mL of distilled water, homogenized on a Twist Shaker (Biofree, Seoul, Korea) for 60 min, and centrifuged at 8000× g for 5 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…[32] Regarding proteases, several studies have demonstrated the positive correlation between amino acid levels and protease activity. [30] Therefore, the increase of amino-type nitrogen contents was related to protease activity (Figure 1c). Cellulase is a complex enzyme with high yield and activity that could degrade stubborn cellulase effectively and generate oligosaccharides of different lengths.…”
Section: Dynamic Changes In Physicochemical Propertiesmentioning
confidence: 90%
“…Overall, the activity of these enzymes increased along with the prolonging of fermentation time, as also observed by other authors. [22,30] Enhancement of enzymatic activity helps to break down the starch, protein and fat in the substrate into small molecules and to change the metabolite profiles found in fermented foods. [31] As one of the most important enzymes in the saccharification stage of rice wine, β-glucosidase produces glucose by destruction of glucosidic linkages in polysaccharides.…”
Section: Dynamic Changes In Physicochemical Propertiesmentioning
confidence: 99%